PHYSICAL EDUCATION AND TEXTBOOK: BETWEEN THE GAP AND THE AWAKENING - Mendonca de Souza Junior, Marcilio Barbosa; Amaral, Lucas Vieira do; Tavares de Melo, Marcelo Soares; Darido, Suraya Cristina [UNESP]; Torres Lima, Ricardo Bezerra (Univ Fed Rio Grande Do Sul, Escola Educ Fisica, 2015)
The textbook also receiving some criticism, hold the potential to contribute to the qualification of the teaching and learning of the various curriculum components. However, it is common to notice that Physical Education has shown that remote resource type material, with some isolated initiatives of using this. In this context, this study aimed to recognize, in the literature, what factors contributed to the formation of the gap between physical education and textbooks and elaborations have been made recently in this field on such a book. We conclude that the historical legacy of Physical Education is one of the main driving factors of this hiatus, but recently began to be minimized by design initiatives and use of the textbook in the field.
Keywords: Textbooks; Teaching materials; Learning